(untitled) (Annals of Medical Research, 2021)
Aim: This research was conducted in order to determine intensive care nurses’ attitudes toward the “dying with dignity” principles and factors affecting.Materials and Methods: This descriptive study was conducted at the Turgut Özal Medical Center of Inonu University from June 2019 to July 2020. Nurses working in intensive care units constituted the population of the research. The research was without sampling choice, and was carried out with 204 nurses who agreed to participate in the research and fit the criteria. The “Personal Information Form” and the “Assessment Scale of Attitudes toward the Principles of Dying with Dignity” were used. Data were analyzed using weight, means, standard deviations, Mann–Whitney U, and Kruskal–Wallis H tests.Results: It was found that the nurses’ “Assessment Scale of Attitudes toward the Principles of Dying with Dignity” score was 45.7±4.25. A negative relationship was found between age and the Assessment Scale of Attitudes toward the Principles of Dying with Dignity score (r:-.181, p0.05). Moreover, it was found that there was a statistically significant difference (p0.05) between the Assessment Scale of Attitudes toward the Principles of Dying with Dignity score and variables such as gender, education level, working time in the profession, knowledge about the concept of “dying with dignity,” and the desire to work in the intensive care unit.Conclusion: It was determined that the nurses’ attitudes toward the principles of dying with dignity were moderate, and various demographic variables had effects on Principles of Dying with Dignity.